Ultrastructural Studies of Sporulation in a Conditionally Temperature-Sensitive Ribonucleic Acid Polymerase Mutant of Bacillus subtilis - Santo, Leatrice (1973)
Morphological studies of a conditionally temperature-sensitive ribonucleic acid polymerase mutant of Bacillus subtilis have revealed that sporulation is inhibited at stage II when the cells are grown at 47.5 C. Growth and sporulation occur normally at 30 C with the mutant. The mutant grows normally at 47.5 C but is prevented from sporulating at the nonpermissive temperature by an abnormal septation during forespore membrane formation which prevents the subsequent engulfment process (stage III). The mutation affects the normal functioning of ribonucleic acid polymerase at the nonpermissive temperature resulting in abortive sporulation.